Крымское ханство в контексте черноморской торговли (XV-XVIII вв.) - Прохоров, Д.А. (Материалы по археологии, истории и этнографии Таврии, 2001)
Предпагаемая статья является попыткой обобщения исторических материалов о развитии внешней и внутренней торговли на лолуострове, а также ремесленного производства в Крымском ханстве. Кроме сообщений и записок путешественников и дипломатов, в разное время лосетивших Крым, в данной работе использовались материалы Центрального Государственного Архива Автономной Республики Крым, а также ряд опубликованных ранее документов, касающихся в той или иной стелени рассматриваемого нами вопроса The problem of the development of foreign and home trade of the Crimean Khanate of the 15th-18th centuries and its role in the trade relations between the countries of the Black Sea region are under consideration in this article. As the result of the analysis of different historic documents, memoirs and reports of the travellers and diplomats who had visited the Crimea, and the materials of the Crimean archives we drew to the following conclusion: commodity circulation in the Black Sea trade the Crimea was of no small importance being the centre of crossing numerous trade routes, and the trade on the peninsula itself acquired a transit character. The main items for export in the Crimean Khanate for centuries were grain, salt and slaves. Trading salt brought the most substantial profit. Russia - Turkey wars at the end of the IS*" century, diplomatic complications in Europe, eviction of Christian population of the Crimea in 1778, mass emigration of the Tatars after annexation of the Crimea to Russia negatively affected the trade and handicraft production. Reviving in the economy of the Crimea began only in 1784.